Circulating yersinia specific immune complexes after acute yersiniosis: a follow up study of patients with and without reactive arthritis. Issue 2 (February 1987) - Lahesmaa-Rantala, R; Granfors, K; Kekomäki, R; Toivanen, A
Abstract : The occurrence of immune complexes (ICs) containing Yersinia enterocolitica antigen and immunoglobulin was studied in 216 serum samples from 51 patients with recent yersiniosis at an early stage of the disease and during a follow up of two to 12 months. Twenty eight of the patients developed reactive arthritis, 23 recovered from the infection without any complications. An enzyme linked immunosorbent assay (ELISA) recently developed for detection of ICs containing yersinia antigen(s) and IgM, IgG, or IgA was applied. During the first two months after onset of the infection yersinia specific IgM complexes were demonstrated in higher concentrations in patients with arthritis than in those not developing this postinfection complication (p less than 0.02). The difference in the occurrence of IgM complexes between the two groups decreased with time. Yersinia specific IgA complexes were demonstrable in four patients with arthritis and in none of the non-arthritic patients. Yersinia specific IgG complexes were occasionally present in both patient groups. Altogether, more than eight months after onset of the infection yersinia specific ICs were detected in six arthritic and two non-arthritic patients, suggesting that in certain individuals yersiniae may hide after the initial infection for prolonged periods.